2008
DOI: 10.1038/ismej.2008.86
|View full text |Cite
|
Sign up to set email alerts
|

Functional metagenomics reveals diverse β-lactamases in a remote Alaskan soil

Abstract: Despite the threat posed by antibiotic resistance in infectious bacteria, little is known about the diversity, distribution and origins of resistance genes, particularly among the as yet unculturable environmental bacteria. One potentially rich but largely unstudied environmental reservoir is soil. The complexity of its microbial community coupled with its high density of antibiotic-producing bacteria makes the soil a likely origin for diverse antibiotic resistance determinants. To investigate antibiotic resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
392
4
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(413 citation statements)
references
References 38 publications
10
392
4
7
Order By: Relevance
“…13 In the present study, a high-throughput qPCR with 295 validated primer sets (including 285 ARGs, 9 transposase genes, and 16S rRNA gene) has been used to investigate the impact of RWI on ARGs in public park soils of representative Chinese cities. Since ARGs can be present naturally, 24,25 the background level needs to be considered. So, soil samples without using reclaimed water were also collected as control for each RWI park soil.…”
Section: ■ Introductionmentioning
confidence: 99%
“…13 In the present study, a high-throughput qPCR with 295 validated primer sets (including 285 ARGs, 9 transposase genes, and 16S rRNA gene) has been used to investigate the impact of RWI on ARGs in public park soils of representative Chinese cities. Since ARGs can be present naturally, 24,25 the background level needs to be considered. So, soil samples without using reclaimed water were also collected as control for each RWI park soil.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, soil samples from six public parks using reclaimed water irrigation were collected. Since antibiotic resistance is ancient (Allen et al, 2009;D'Costa et al, 2011), four pristine soil samples from Natural Scenic Resort of Ling Mountain not using reclaimed water were collected as control. The objective of this study was to evaluate whether the soil in public parks receiving reclaimed water acts as a reservoir of ARGs and has the potential for transferring ARGs to human pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…2b). In fact, previous studies have recognized soil as a reservoir for a broad spectrum of β-lactamases, irrespective of human activities (Demaneche et al 2008;Allen et al 2009). The β-lactamases are among the most abundant ARGs commonly found in soils (Forsberg et al 2014) and clinical settings (Jacoby and Munoz-Price 2005), and seem to be ancient, being present in soil long time before the antibiotic era (Hall, Salipante and Barlow 2004).…”
Section: Temporal Patterns Of Soil Args and Stimulation Of β-Lactam-rmentioning
confidence: 99%
“…The β-lactamases are among the most abundant ARGs commonly found in soils (Forsberg et al 2014) and clinical settings (Jacoby and Munoz-Price 2005), and seem to be ancient, being present in soil long time before the antibiotic era (Hall, Salipante and Barlow 2004). The β-lactam class of antibiotics, such as penicillins, and cephalosporins, are frequently prescribed antibiotics for humans and livestock (Allen et al 2009). In this study, none of these β-lactamases were found to be enriched in the manure samples; however, several β-lactamases (the Per-1, Per-2, IMP-2 and IMP-5 groups in the arable soil, whereas Per-1, SFO-1, IMP-2 and IMP-5 groups in the pasture soil), which are common in clinical isolates (e.g.…”
Section: Temporal Patterns Of Soil Args and Stimulation Of β-Lactam-rmentioning
confidence: 99%
See 1 more Smart Citation